Vocabulary, Metalinguistic Awareness and Language Dominance Among Bilingual Preschool Children - Altman, Carmit; Goldstein, Tamara; Armon-Lotem, Sharon (Frontiers in Psychology, 2018)
Awareness of language structure has been studied in bilinguals, but there is limited research on how language dominance is related to metalinguistic awareness, and whether metalinguistic awareness predicts vocabulary size. The present study aims to explore the role of language dominance in the relation between vocabulary size in both languages of bilingual children and metalinguistic awareness in the societal language. It evaluates the impact of two metalinguistic awareness abilities, morphological and lexical awareness, on receptive and expressive vocabulary size. This is of special interest since most studies focus on the impact of exposure on vocabulary size but very few explore the impact of the interaction between metalinguistic awareness and dominance. 5–6-year-old preschool children with typical language development participated in the study: 15 Russian-Hebrew bilingual children dominant in the societal language (SL) Hebrew, 21 Russian-Hebrew bilingual children dominant in the Heritage language (HL) Russian and 32 monolingual children. Dominance was determined by relative proficiency, based on standardized tests in the two languages. Tasks of morphological and lexical awareness were administered in SL-Hebrew, along with measures of receptive and expressive vocabulary size in both languages. Vocabulary size in SL-Hebrew was significantly higher for SL-dominant bilinguals (who performed like monolinguals) than for HL-dominant bilinguals, while HL-Russian vocabulary size was higher for HL-dominant bilinguals than for SL-dominant bilinguals. A hierarchical regression analyzing the relationship between vocabulary size and metalinguistic awareness showed that dominance, lexical metalinguistic awareness and the interaction between the two were predictors of both receptive and expressive vocabulary size. Morphological metalinguistic awareness was not a predictor of vocabulary size. The relationship between lexical awareness and SL-vocabulary size was limited to the HL-dominant group. HL-dominant bilinguals relied on lexical metalinguistic awareness, measured by fast mapping abilities, that is, the abilities to acquire new words, in expanding their vocabulary size, whereas SL-dominant bilinguals and monolinguals did not. This difference reflects the milestones of lexical acquisition the different groups have reached. These findings show that metalinguistic awareness should also be taken into consideration when evaluating the variables that influence vocabulary size among bilinguals though different ways in different dominance groups.